What's black and white and Reid all over? : something hilarious happened at the library - Reid, Rob. 1955- (American Library Association, 2012)
Reid shows you how to share humor with children, in order to connect them to literature and imagination. The programs and the books he uses are kid-tested and ready for you to share.